2003
DOI: 10.1021/bm025740+
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Virus−Polymer Materials. 1. Synthesis and Properties of PEG-Decorated Cowpea Mosaic Virus

Abstract: Cowpea mosaic virus was derivatized with poly(ethylene glycol) to give well-controlled loadings of polymer on the outer surface of the coat protein assembly. The resulting conjugates displayed altered densities and immunogenicities, consistent with the known chemical and biological properties of PEG. These studies make CPMV potentially useful as a tailored vehicle for drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
189
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(197 citation statements)
references
References 28 publications
5
189
0
Order By: Relevance
“…We have previously shown that unmodified CPMV capsids induce antibody responses [47], and here we report that an increase in B-cell number is observed in spleen following intravenous administration of CPMV. A similar increased B-cell infiltration was also reported in mice following Qβ phage particle intravenous administration [19].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have previously shown that unmodified CPMV capsids induce antibody responses [47], and here we report that an increase in B-cell number is observed in spleen following intravenous administration of CPMV. A similar increased B-cell infiltration was also reported in mice following Qβ phage particle intravenous administration [19].…”
Section: Discussionsupporting
confidence: 66%
“…We previously showed that a strong immune response is mounted in mice against CPMV particles, and that a modest polyethylene glycol (PEG) coating inhibits the induction of the anti-CPMV response [47] as well as reduce virus uptake in endothelial cells, liver and spleen [29]. Interestingly, preliminary studies indicate that coating of CPMV particles with 2000 MW PEG doubles the plasma circulation time (Destito et al, unpublished observation), likely by inhibiting the interaction with endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…346 The resulting hybrids had physical and immunogenic properties that were markedly different from those of the native virus. Furthermore, the PEGylation reaction could be used to block the binding of a blue fluorescent antibody to its antigen (stilbene), which was also bound to the cysteine residues on the CPMV surface (Scheme 14).…”
Section: Cage-structured Virusesmentioning
confidence: 99%
“…In addition to acting as a diagnostic agent, particle-based MR contrast agents may also be loaded with therapeutics for use in targeted drug or gene delivery. Examples of compounds suitable for this purpose are polymerized liposomes (10), perfluorocarbon-based vesicles (11), and viral protein cages (12,13). Further development of materials that combine both targeted drug delivery and MR imaging capability is a desirable long-term goal.…”
mentioning
confidence: 99%
“…The outer surfaces of viruses have been shown to be a robust platform for attachment of inorganic materials (20,21) and organic ligands including peptides (22), fluorescent labels (21,23,24), and epitopes for antigen presentation (25). The immune response that is caused by some viruses has also been shown to be reduced by functionalizing the exterior surface with polyethylene glycol (13,26). The inner surface of viral cages can also be utilized for chemically specific encapsulation of organic and inorganic materials (12,18,27).…”
mentioning
confidence: 99%